Efficacy of herbal essential oils at tetrahlormethane induced hepatitis in laboratory rats - Antonenko, Petro; Antonenko, P. P.; Antonenko, P.; Антоненко, Петро Павлович; Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; et al. (Scientific Society Anatomists, Histologists, and Embryologists, 2020)
In this paper, the efficacy of essential oils in the composition of Fitohol herbal medicinal product against the background of tetrachloromethane induced toxic hepatitis in laboratory rats has been studied. It was established that the injection of Fitohol in rats at the dose of 0.03 g per 100 g of body weight positively influenced the clinical condition of animals, facilitated the manifestation of hepatocellular failure and the development of destructive changes in hepatocytes (reducing the activity of alkaline phosphatase, alanine and aspartate aminotransferases in blood plasma and oxyproline, hexosamines and malonic dialdehyde in liver homogenates) in acute toxic hepatitis. In the long-term intoxication of rats with CCl4, the effect of Fitohol was manifested in improving the functional state of the hepatobiliary system and some restoration of the protein- synthesizing liver function. У цій роботі досліджена ефективність ефірних масел у складі рослинного лікарського засобу Фитохол на тлі токсичного гепатиту, викликаного тетрахлорметаном, у лабораторних щурів. Встановлено, що ін’єкція фітохолу щурам у дозі 0,03 г на 100 г маси тіла позитивно впливала на клінічний стан тварин, сприяла прояву гепатоцелюлярної недостатності та розвитку деструктивних змін у гепатоцитах (зниження активності лужних речовин фосфатаза, аланін та аспартатамінотрансферази у плазмі крові та оксипролін, гексозаміни та малоновий діальдегід у гомогенатах печінки) при гострому токсичному гепатиті.
Ефективність рослинних ефірних олій за тетрахлорметанового гепатиту в лабораторних щурів
Антоненко Петро Павлович https://orcid.org/0000-0003-1469-0121 Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Cуслова Наталія Іванівна https://orcid.org/0000-0001-9500-9224 Скляров Павло Миколайович https://orcid.org/0000-0002-4379-9583 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: white rats; білі щури; herbal medicinal product; рослинний лікарський засіб; tetrachloromethane induced toxic hepatitis; токсичний гепатит, індукований тетрахлорметаном; blood plasma; плазма крові; liver homogenate; гомогенат печінки